Operaciones básicas y su influencia en la resolución de problemas matemáticos en los estudiantes de 5to año de educación general básica de la Escuela Particular “Nueva Era” del cantón Vinces Provincia “Los Ríos” - Sumba Mejia, Gloria Stefhany (2019)
This research aims to present a proposal for improvement in the mathematical area for fifth-year students of the private school "NUEVA ERA" The study begins with a direct observation and survey, a sample of 17 students aged between 9 and 10 years. Knowledge in mathematics is sense through problem solving, this statement is so true that it regards this latter as the heart of the discipline. In recent decades has accentuated the concern that mathematical problems resolution is applied really as an activity of thought because it is frequent that teachers work in the classroom routine problems which are far from stimulating cognitive effort of learners. For this reason it is necessary to design teaching strategies that require students to understand and solve mathematical problems, based on the application of basic operations